TH

tìm x :\(\frac{x+2016}{-3}=\frac{-12}{x+2016}\)

CT
7 tháng 4 2019 lúc 20:58

trả lời

nhân chéo lên là làm đc nha bn

hok tốt

Bình luận (0)
VN
7 tháng 4 2019 lúc 21:01

\(\frac{x+2016}{-3}=-\frac{12}{x+2016}\)

\(\Rightarrow\left(x+2016\right)^2=-3.\left(-12\right)\)

\(\Rightarrow\left(x+2016\right)^2=36\)

\(\Rightarrow\left(x+2016\right)^2=6^2\)

\(\Rightarrow x+2016=6\)

\(\Rightarrow x=6-2016\)

\(\Rightarrow x=-2010\)

Bình luận (0)
HS
7 tháng 4 2019 lúc 21:05

\(\frac{x+2016}{-3}=\frac{-12}{x+2016}\)

\(\Leftrightarrow(x+2016)\cdot(x+2016)=(-12)\cdot(-3)\)

\(\Leftrightarrow(x+2016)^2=36\)

\(\Leftrightarrow(x+2016)^2=6^2\)

\(\Leftrightarrow x+2016=\pm6\)

\(\Leftrightarrow\hept{\begin{cases}x+2016=6\\x+2016=-6\end{cases}}\Leftrightarrow\hept{\begin{cases}x=-2010\\x=-2022\end{cases}}\)

Do đó,\(x\in\left\{-2010;-2022\right\}\)

Bình luận (0)
TH
7 tháng 4 2019 lúc 21:07

Theo đề bài ta có :

(x+2016) . (x+2016) = -3 . (-12)

(x+2016)2 = 36

Ta có (x+2016)2= 62

Trường hợp 1:                                                                                                        

x+2016=6

x          = 6-2016

x          = -2010

Trường hợp 2:

x+2016= -6

x          = -6-2016

x          = -2022

Vậy x = -2010; x= -2022

k mk nhé

Bình luận (0)
LH
7 tháng 4 2019 lúc 21:09

suy ra (x+2016).(x+2016)=(-3).(-12)

            (x+2016)^2          =36

            x+2016=6 suy ra x=-2010

   hoặc  x+2016=-6 suy ra x=-2022

vậy x=-2010 hoặc x=-2022

Bình luận (0)
NH
7 tháng 4 2019 lúc 21:09

nhân tích chéo ta được

(x+2006).(x+2006)=(-3).(-12)

(x+2006)^2=36

hay(x+2006)^2=6^2

      x+2006=6

                x=6-2006

               x=-2000

Bình luận (0)